NUEVOS ESTATUTOS DE AUTONOMÍA CON VIEJOS SISTEMAS ELECTORALES - Miguel Ángel Presno Linera (Revista d'Estudis Autonòmics i Federals, 2007)
The purpose of this paper is to analyse the effect of the recent reforms of theAutonomous Statutes on the electoral system of the Autonomous Communities,based on the material rules (gender equality, electoral debates, etc.) and proceduralrules (a qualified majority to approve the electoral bill) which theyincluded. The new Autonomous Statutes display a twofold mistrust. First,there is mistrust of the Central Parliament and its General Electoral Bill, dueto its heavy regulation of regional elections. Second, there is mistrust of theParliament of the Autonomous Community, which is restricted in two ways:a) by including the subjects that should be in an electoral bill in the AutonomousStatute; b) by means of the “consensus trap”, which requires a high level ofagreement among Parliamentary groups in order to pass the electoral bill,which in all likelihood will prevent the changes from being made, as the politicaland institutional future of the groups involved is at stake.If we add two further factors (the application of 116 articles the GeneralElectoral Bill to the autonomous elections and the Autonomous Statute regulation on electoral matters), and we discount one factor (the lack of innovationin the autonomous regional system), it is clear that the Electoral Billsof the Autonomous Communities will be redundant, too detailed and willcover too little. In conclusion, we have new Autonomous Statutes but oldelectoral systems.